2015
DOI: 10.1186/s12885-015-1426-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of second primary malignancies following uterine cancer: a population-based study in Taiwan over a 30-year period

Abstract: BackgroundPrevious studies assessing second primary malignancies (SPMs) after uterine cancer have been conducted in Western populations with conflicting results. This study aimed to define the incidence and risk of SPMs in Taiwanese patients with an initial diagnosis of uterine cancer.MethodsUsing population-based data from the Taiwan Cancer Registry for the period 1979–2008, we quantified standardized incidence ratios (SIRs) among 11,571 women with an initial diagnosis of uterine cancer.ResultsAmong the 11,57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 34 publications
(45 reference statements)
4
24
0
Order By: Relevance
“…This study revealed that the incidence rate of MPC with endometrial and ovarian cancer, which was evaluated using the autopsy database, was significantly high. Similar findings were reported from different populations in various regions, for example, Swede, Turk, and Taiwanese . The incidence between MPC with endometrial and ovarian cancers and those without these cancers was associated with the changes in the female endocrine system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed that the incidence rate of MPC with endometrial and ovarian cancer, which was evaluated using the autopsy database, was significantly high. Similar findings were reported from different populations in various regions, for example, Swede, Turk, and Taiwanese . The incidence between MPC with endometrial and ovarian cancers and those without these cancers was associated with the changes in the female endocrine system.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported from different populations in various regions, for example, Swede, 24 Turk, 25 and Taiwanese. 26 The incidence between MPC with endometrial and ovarian cancers and those without these cancers was associated with the changes in the female endocrine system. Several cohorts demonstrated that the increased number of births reduced the risks of endometrial and/or ovarian cancer, 27,28 whereas hormone replacement therapy (HRT) significantly increased the risk of endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of second ovarian cancer is increased in young patients with primary uterine cancer . Hung et al.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of second ovarian cancer is increased in young patients with primary uterine cancer [12,13]. Hung et al [14] found that patients with primary ovarian cancer also have an increased risk of second uterine cancer, but Levi showed that patients with ovarian cancer did not have any excess risk of any second cancer in his study that recruited 1530 subjects [15].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of uterine cancer in Taiwan is also favorable. A population‐based study reported that median survival was 24.50 years and the 5‐year survival rate was 80% . Therefore, uterine cancer could be considered as a chronic condition because of the favorable outcome.…”
Section: Introductionmentioning
confidence: 99%